2016
DOI: 10.1177/1071100716651963
|View full text |Cite
|
Sign up to set email alerts
|

Case Series With Histopathologic and Radiographic Analyses Following Failure of Fresh Osteochondral Allografts of the Talus

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A difference was found in the autograft versus the allograft procedure with success rates of 90 and 55%, respectively. Differences in these procedures have been previously highlighted in the literature [ 4 , 34 , 35 , 44 ]. Since an allograft procedure is typically used for larger defects, it is to be expected that a difference in success percentage was likely to be found.…”
Section: Discussionmentioning
confidence: 99%
“…A difference was found in the autograft versus the allograft procedure with success rates of 90 and 55%, respectively. Differences in these procedures have been previously highlighted in the literature [ 4 , 34 , 35 , 44 ]. Since an allograft procedure is typically used for larger defects, it is to be expected that a difference in success percentage was likely to be found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a CD4+ and CD8+ lymphocyte-mediated failure mechanism has recently been reported to be responsible for failure in a fresh osteochondral allograft of the talus. 13 However, no study has reported like rejection in the knee, and it seems that the subtle immune reaction does not carry any clinical consequence in most cases. 14 In this sense, a careful resection of the unnecessary soft tissue and pulsed lavage cleansing 9 of the graft for 5 to 10 minutes might help to decrease graft immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a small case series of clinically failed, retrieved OCA grafts, histologic analysis showed the presence and colocalization of CD4+ and CD8+ T cells. 74…”
Section: Factors Influencing Failure Of Fresh Osteochondral Allograftmentioning
confidence: 99%